Development of natural regeneration after different regeneration cuttings in a Norway spruce peatland forest in northern Finland - Hökkä, Hannu; Miettinen, Janne; Karhu, Jouni (Springer Nature, 2025)
As the clearcutting of peatland forests is known to cause harmful consequences especially for the water environment, there is increasing interest in alternative natural regeneration methods. We studied the regeneration stocking development on a southern Lapland site, where shelterwood cutting, heavy selection cutting, patch clearcutting (≤ 0.3 ha) treatments, and a non-treated control with three replicates had been established in the winter of 2013. Regeneration stocking was inventoried in the springs of 2013, 2016, 2018, and 2021 from 16 seedling survey plots (size 5 m2), which were systematically located in each of the 12 treatment plots. The number of small spruce seedlings (< 10 cm height) was largest in 2016 and then started to decrease. The number of large (> 10 cm) spruce seedlings increased two- to three-fold (4,500–9,000 ha− 1) towards the end of the study period for all cutting treatments. The number of large birch seedlings also increased especially for heavy selection and clearcutting and was 2–10 times higher than that of spruce. Birch was less abundant in shelterwood cutting. The tallest spruce and birch seedlings were found in clearcuts. Large spruce and birch seedlings were most evenly distributed for heavy selection and clearcut treatments. All cutting treatments showed high average regeneration density for a mixed seedling stand of Norway spruce and downy birch within the eight post-cutting years.
Keywords: advance growth; Betula pubescens; natural regeneration; peatlands; Picea abies; shelterwood; selection cutting